2019
DOI: 10.4236/ojn.2019.92014
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Records Implementation Readiness: An Integrative Review

Abstract: Purpose: The purpose of this review was to discuss the status of evidence related to the assessment of readiness of healthcare facilities for e-health initiatives implementation, specifically the common Electronic Health Record (EHR) systems. Methods: An integrative review approach was utilized. The databases of Google Scholar, Scopus, Science Direct, PubMed, Medline, CINAHL, Ovid, ProQuest, and EBSCO host were searched for related evidence published between 2000 and 2018. Results: Seventeen studies were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…The Medical Research Council’s framework for developing and evaluating complex interventions states that taking account of context is crucial to implementation [39]. Most effort in preparing for EHR implementation are directed towards organisational readiness, including staff readiness [40]. A recent review reported that for 95% of included studies, users were the primary barrier to implementation [41], and an additional review highlighted the importance of human factors in the success of, and barriers to implementation [42].…”
Section: Introductionmentioning
confidence: 99%
“…The Medical Research Council’s framework for developing and evaluating complex interventions states that taking account of context is crucial to implementation [39]. Most effort in preparing for EHR implementation are directed towards organisational readiness, including staff readiness [40]. A recent review reported that for 95% of included studies, users were the primary barrier to implementation [41], and an additional review highlighted the importance of human factors in the success of, and barriers to implementation [42].…”
Section: Introductionmentioning
confidence: 99%
“…Ketidaksiapan penerapan RME di fasilitas kesehatan dapat menimbulkan banyak hambatan selama proses penerapan. Hal ini juga dapat menyebabkan rendahnya adopsi tenaga kesehatan dalam menggunakan sistem RME (Alsadi and Saleh, 2019). Oleh karena itu, penerapan RME harus disetujui oleh seluruh pengguna RME karena peran mereka yang sangat penting dalam sistem kesehatan (Masyfufah et al, 2022).…”
Section: Pendahuluanunclassified
“…Implementing a health information system such as an EHR can potentially improve the performance of healthcare facilities, save operational costs, and improve patient satisfaction [7]. Implementing the EHRs provides promising evidence-based healthcare, higher levels of service completeness, accuracy, validity, access, and coordinated communication of patient information, safe prescription, utility of electronic health records for clinical diagnosis, adequate clinical decision support, and improved efficiency of medical practices [8]. The research team successfully developed and implemented electronic medical records in previous studies called Eposyandu [9] and Electronic Health Records (EHRs) in a family's health home clinic of Jember district [10].…”
Section: Introductionmentioning
confidence: 99%